Total Fat, Calcium (Ca), Iron (Fe) and Zinc (Zn) Contents During Ecdysis process in the Crabs (Scylla serrata, Forsskal) - Sri Swasthikawati; Rarastoeti Pratiwi; Trijoko . (Jurnal Sain Veteriner, 2014)
Crab is one of the most abundant marine animals in Indonesia. Crabs not only rich of nutrient, but also have commercial value. Today, there is an innovation in crab aquaculture use ecdysis mechanism, known as soft shell crab. However, the limited studies about biochemical and nutritional composition of this crab remain to be explored. The aims of this research were to understand total fat, calcium, iron, and zinc contents of crab (Scyllaserrata) during ecdysis process until being soft shell crab comparing to the hard shell crab from the same species. This research was done using crab Scylla serrata, male, weighing ± 150-180 gr, completely randomized design with four variations of treatment, during 8 days, 16 days, soft shell crab, and control, repeated 3 times. Samples from each treatment were grown and were prepared for the chemical analysis. Total fat was measured usingSoxhlet method with chloroform and methanol (1:2, v/v) as solvent. Atomic absorption spectrometer was used to measure calcium, iron, and zinc contents. Then, the result were analyzed using one way Anova and Duncan 5 %. The results showed that the total fat, calcium and zinc contents of soft shell crab Scylla serrata were higher and significantly different with three other treatments. It could be concluded that the ecdysis process, raised total fat, calcium and zinc contents of crab Scylla serrata. The total fat, calcium, and zinc contents of soft shell crab Scylla serrata was higher than that of hard shell crab from the same species.